2001
DOI: 10.1002/joc.658
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Standardized Precipitation Index, the China‐Z Index and the statistical Z‐Score

Abstract: The Standardized Precipitation Index (SPI) was developed to detect drought and wet periods at different time scales, an important characteristic that is not accomplished with typical drought indices. More and more users employ the SPI to monitor droughts. Although calculation of the SPI is easier than other drought indices, such as the Palmer Drought Index, it is still relatively complex. In China, an index called the China-Z Index (CZI) has been used since 1995 by the National Climate Centre of China to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
194
0
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(246 citation statements)
references
References 7 publications
3
194
0
13
Order By: Relevance
“…For example, at geographic locations whereq is larger than 0.5, the gamma distribution parameters are being estimated by fewer than 18 samples (out of 36 years) and the parameter reliability becomes quite suspect. Research applying estimated distribution parameters suggests that over 30 years of data be used in the estimation of parameters (McKee, 1993;Hayes et al, 1999;Wu et al, 2001).…”
Section: Incorporating the Occurrence Of No Rainfallmentioning
confidence: 99%
“…For example, at geographic locations whereq is larger than 0.5, the gamma distribution parameters are being estimated by fewer than 18 samples (out of 36 years) and the parameter reliability becomes quite suspect. Research applying estimated distribution parameters suggests that over 30 years of data be used in the estimation of parameters (McKee, 1993;Hayes et al, 1999;Wu et al, 2001).…”
Section: Incorporating the Occurrence Of No Rainfallmentioning
confidence: 99%
“…SPI based drought identification has been utilized by [4] to monitor the 1996 drought in the United States of America. Although it is quite a recent index, the SPI was used in Turkey [5], Argentina [6], Canada [7], Spain [8], Korea [9], Hungary [10], China [11] and Europe [12] for real time monitoring or retrospective analysis of droughts. NDVI-rainfall relationship was also used in monitoring drought on a large scale in north east Thailand [13], East Asia [14] and the Central Great Plains of US [15] using NOAA/AVHRR data.…”
Section: Introductionmentioning
confidence: 99%
“…Many drought indices have been developed to date. These include the Palmer Drought Severity Index (PDSI) (Palmer, 1965), which is widely used in the USA, the Deciles Index (Gibbs and Maher, 1967), which is operational in Australia, the China-Z Index (CZI), which is used by the National Metrological Center of China (Wu et al, 2001), Standardized Precipitation Index (SPI) (McKee et al, 1993), which has gained world popularity, etc. The review of drought indices can be found in several sources (e.g.…”
Section: Introductionmentioning
confidence: 99%